Magnetic Microscopy of Nanostructures - Hopster, Herbert.; Hopster, Herbert.; Oepen, Hans Peter.; Oepen, Hans Peter. (NanoScience and Technology,, 2005)
This volume contains a comprehensive collection of overview articles on novel microscopy methods for imaging magnetic structures on the nanoscale. Written by leading scientists in the field the book covers synchrotron based methods, spin polarized electron methods, and scanning probe techniques. It will be a valuable source of reference for graduate students and newcomers to the field.